2022
DOI: 10.1108/wwop-11-2021-0055
|View full text |Cite
|
Sign up to set email alerts
|

Differentials and predictors of hospitalisation among the elderly people in India: evidence from 75th round of National Sample Survey (2017-2018)

Abstract: Purpose There is limited evidence on the determinants of hospitalisation and its causes in India. This study aims to examine the differential in the hospitalisation rates and its socioeconomic determinants. This study also examines the causes of diseases in hospitalisation among the elderly (≥60 years) in India. Design/methodology/approach This study used data from the 75th round of the National Sample Survey Organizations, collected from July 2017 to June 2018. The elderly samples in this survey are 42,759,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 48 publications
4
10
0
Order By: Relevance
“…In contrast, the recent SRS report (2019) found that, with the exception of Kerala, all other southern states (Tamil Nadu, Telangana, Karnataka, and Andhra Pradesh) had below the national average percentage of medical attention before death (SRS Report, 2019). On the other hand, our finding has also revealed that Eastern region is significantly more likely to receive medical attention before death which is also an exceptional result while previous studies showed a contradictory results (Akhtar & Saikia, 2022; Pandey et al, 2017a, 2017b). Even, the SRS report (2019) has documented that except Odisha, all other easter states (West Bengal, Bihar and Jharkhand) had lower percentage of receiving medical attention before death for all ages than the national average (SRS Report, 2019).…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…In contrast, the recent SRS report (2019) found that, with the exception of Kerala, all other southern states (Tamil Nadu, Telangana, Karnataka, and Andhra Pradesh) had below the national average percentage of medical attention before death (SRS Report, 2019). On the other hand, our finding has also revealed that Eastern region is significantly more likely to receive medical attention before death which is also an exceptional result while previous studies showed a contradictory results (Akhtar & Saikia, 2022; Pandey et al, 2017a, 2017b). Even, the SRS report (2019) has documented that except Odisha, all other easter states (West Bengal, Bihar and Jharkhand) had lower percentage of receiving medical attention before death for all ages than the national average (SRS Report, 2019).…”
Section: Discussionsupporting
confidence: 65%
“…Surprisingly, our result has revealed that Southern and Western regions are found to have significantly less likely to receive medical attention before death among deceased adults which is a striking finding. While the previous studies have found that older adults belong to Southern region were more likely receive hospitalizations (Akhtar & Saikia, 2022; Banerjee, 2021; Giridhar et al, 2014; Pandey et al, 2017a, 2017b). In contrast, the recent SRS report (2019) found that, with the exception of Kerala, all other southern states (Tamil Nadu, Telangana, Karnataka, and Andhra Pradesh) had below the national average percentage of medical attention before death (SRS Report, 2019).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Though Central region has a shorter life expectancy and a smaller proportion of older individuals than the Northern region (SRS Report, 2019). In the Central region, poor health-care facilities and negligence of visiting health care centres are also linked to a higher death risk among older adults (Akhtar & Saikia, 2022; Banerjee, 2021). As a result, it is recommended that each state in the central region emphasize the importance of disease prevention and control, raise disease prevention awareness, and develop strategic scientific measures to reduce mortality risks and control critical areas and populations while taking into account the current situation in the region.…”
Section: Discussionmentioning
confidence: 99%